2023
DOI: 10.1177/03331024231209309
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and migraine in adolescence: A nationwide study

Yair Zloof,
Avishai M. Tsur,
Maya Simchoni
et al.

Abstract: Background The association between body mass index (BMI) and migraine in adults has been well established. However, studies in children and adolescents are inconclusive. We aimed to study the association between BMI and migraine using a national dataset that comprises the electronic medical records of more than two million adolescents. Methods This study included all Israeli adolescents (57.7% males, 42.3% females; mean age 17 years) who were medically assessed before mandatory military service during 1990-202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A meta-analysis of eight studies, including 16,556 patients, showed no association between overweight, obesity, and migraine among adolescents ( 32 ). However, a recent study showed that both underweight and obesity were associated with migraine among adolescents ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of eight studies, including 16,556 patients, showed no association between overweight, obesity, and migraine among adolescents ( 32 ). However, a recent study showed that both underweight and obesity were associated with migraine among adolescents ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that headache is the leading reported cause of school absenteeism among children and adolescents ( 7 ). Although the exact etiology of primary headache disorders among adolescents is not yet fully understood ( 8 ), several factors, such as age ( 7 , 9 ), sex ( 4 , 10 , 11 ), obesity, underweight ( 12 ), anxiety/depression ( 11 , 13 , 14 ), and sleep disorders ( 11 , 15 ) are associated with primary headache disorders among children and adolescents. Recent reports show varied primary headache disorders rates among adolescents in different countries ( 3 , 7 , 9 11 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation